Carbon material with sulfur grafted on surface and preparation method thereof

By introducing topological defects on the surface of carbon materials and grafting short-chain sulfur in the form of C-S covalent bonds, the instability problem caused by physical mixing of carbon materials and elemental sulfur in carbon nanotube/sulfur composite positive electrode materials is solved, and a higher level of Stability and reactivity are suitable for a variety of carbon materials.

CN119284880APending Publication Date: 2025-01-10SUN YAT SEN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411688499.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the prior art, the carbon material and elemental sulfur in the grafted carbon nanotube/sulfur composite positive electrode material are compounded in a physically mixed manner, resulting in unstable electrodes.

Method used

By modifying the carbon material in the protection gas, introducing reaction sites, and grafting short-chain sulfur on the surface of the carbon material through C-S covalent bonds to form a carbon material with surface grafted sulfur, avoiding physical mixing methods complex.

Benefits of technology

It improves the topological defect concentration on the surface of carbon materials, increases the active site of short-chain sulfur, enhances the stability and reactivity of the material, is suitable for various carbon materials, retains the original structural characteristics, and improves the electrode performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284880A_ABST
    Figure CN119284880A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of carbon materials, and discloses a carbon material with sulfur grafted on the surface and a preparation method thereof.The preparation method comprises the steps that in protective gas, nitrogen-containing small molecules and / or sulfur-containing small molecules are used for conducting heteroatom doping on the carbon material at the temperature of 600-800 DEG C and calcination at the temperature of 900-1400 DEG C in sequence, and the surface topological defect modified carbon material is obtained; and in protective gas, mixing the prepared surface topological defect modified carbon material with elemental sulfur, and carrying out heat treatment at 150-400 DEG C for 4-40 hours to obtain the carbon material with the surface grafted with sulfur. Reaction sites are introduced to the surface of the carbon material through topological defect modification, then active short-chain sulfur reacts to the surface of the carbon material in a C-S covalent bond mode through covalent bond cooperation, and the introduced short-chain sulfur is more stable and has higher reaction activity and different reaction characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon materials, and in particular relates to a carbon material with sulfur grafted on the surface and a preparation method thereof. Background Art

[0002] Carbon materials have low cost, good electrical conductivity, high specific surface area, adjustable skeleton structure and pore structure, and have been widely used in energy storage and conversion, adsorption separation and biomedicine, and are one of the hot research topics in the field of materials science. The structure of carbon materials has a crucial influence on their application performance. 2 and sp 3 The carbon skeleton formed by the arrangement of hybrid carbon atoms is the structural basis of carbon materials. The carbon skeleton lacking heteroatom doping mainly exhibits non-polar properties, which is not conducive to the carbon material itself participating in physical or chemical reactions. Therefore, it is generally necessary to modify the structure or carbon skeleton of carbon materials through different means, such as starting from the design of carbon precursors, and regulating the structure and carbon skeleton of carbon materials through bottom-up strategies, introducing functional components into the materials; or post-modifying carbon materials, doping metal atoms or heteroatoms into the carbon material skeleton; or compounding carbon materials with other materials. Although these strategies have alleviated the shortcomings of carbon materials themselves to a certain extent, there is still much room for improvement.

[0003] Surface modification strategy is one of the means of modifying carbon materials in recent years. By functionalizing the surface of carbon materials through post-modification strategy, the internal structure of the already preferred carbon materials can be retained. On this basis, the surface structure of the materials can be designed, which is expected to achieve hierarchical design of materials. However, the common surface modification strategy of carbon materials through coating means has shortcomings. Due to the lack of strong interaction between the coating and the surface of the carbon material, the functional coating has poor stability and certain requirements for the groups on the surface of the carbon material. There are also literature reports on the use of grafted nano-carbon fiber / sulfur composite materials as positive electrode materials (refer to Chinese patent CN103247786A), which is composed of grafted carbon nanotubes with a conductive network structure and elemental sulfur melt composite; the preparation method of the grafted carbon nanotube sulfur composite positive electrode material is as follows: (1) synthesizing a grafted carbon nanotube with a network structure having good conductive properties; (2) mixing the prepared grafted carbon nanotube with a network structure and elemental sulfur in a stoichiometric ratio, placing it in a high-pressure steel tank with a ceramic liner, heating to melt the sulfur, and compounding to obtain a grafted carbon nanotube / sulfur composite positive electrode material with a cross-linked network structure. However, the carbon material itself and elemental sulfur in the grafted carbon nanotube / sulfur composite positive electrode material are still physically mixed and composited, and the electrode is unstable after being formed. Summary of the invention

[0004] The present invention provides a carbon material with surface grafted sulfur and a preparation method thereof, which solves the problem that the grafted carbon nanotube / sulfur composite positive electrode material prepared in the prior art is still composited by physically mixing the grafted carbon nanotube and elemental sulfur, and is unstable after forming an electrode.

[0005] The first aspect of the present invention provides a method for preparing a carbon material with surface grafted sulfur, comprising:

[0006] In a protective gas, the carbon material is doped with nitrogen-containing small molecules and / or sulfur-containing small molecules at 600-800° C. and calcined at 900-1400° C. to obtain a carbon material with surface topological defects modified;

[0007] In a protective gas, the prepared carbon material modified with surface topological defects is mixed with sulfur element and then heat treated at 150-400° C. for 4-40 hours to obtain a carbon material with surface grafted sulfur.

[0008] The present invention introduces reaction sites on the surface of the carbon material through topological defect modification, and then reacts the active short-chain sulfur to the surface of the carbon material in the form of CS covalent bonds through covalent bonding: first, heteroatoms are doped in the carbon skeleton at low temperature, and then the doped heteroatoms are removed at high temperature to form partial topological defects with double bonds, which is conducive to the grafting of short-chain sulfur; by controlling the temperature of heteroatom doping and removal, the topological defect modification of the carbon material occurs only on the surface, the original internal structure of the carbon material is retained, the original characteristics are maintained, and the concentration of topological defects on the surface of the carbon material is increased. The higher the concentration, the more active sites that can graft short-chain sulfur, and the corresponding grafted short-chain sulfur content is also higher.

[0009] Preferably, the protective gas is one or more of nitrogen, argon and helium.

[0010] Preferably, the protective gas flow rate is 100-300 mL min -1 .

[0011] Preferably, the mass ratio of the nitrogen-containing small molecules and / or sulfur-containing small molecules to the carbon material is 1:0.5-2.

[0012] Further preferably, the mass ratio of the nitrogen-containing small molecules and / or sulfur-containing small molecules to the carbon material is 1:1.

[0013] Preferably, the nitrogen-containing small molecule and / or sulfur-containing small molecule is one or more of melamine, urea, thiourea, cyanamide and dicyandiamide.

[0014] Preferably, the carbon material is one or more of hard carbon, soft carbon, graphite, nano-carbon material, and silicon carbon.

[0015] Preferably, the heteroatom doping holding time is 1 to 4 hours, and the calcination holding time is 1 to 4 hours.

[0016] Preferably, the heating rate of the heteroatom doping and calcination is 2-5°C·min -1 .

[0017] Preferably, the mass ratio of the carbon material modified with surface topological defects to elemental sulfur is 1:0.5-10.

[0018] Preferably, the prepared surface topological defect modified carbon material is mixed with sulfur element and then heat treated at 150-180° C. for 2-20 h, and then heat treated at 200-400° C. for 2-20 h.

[0019] Firstly, heat treatment is performed at 150-180°C for 2-20h to uniformly mix the material with elemental sulfur, and then heat treatment is performed at 200-400°C for 2-20h to ensure that the elemental sulfur ring opens and reacts with the topological defects, and the short-chain sulfur is not broken by thermal decomposition.

[0020] Remove excess sulfur from the mixture to prevent it from participating in the reaction first when used as an electrode, thereby affecting the electrode performance.

[0021] Preferably, the carbon material is first subjected to surface oxidation enrichment treatment, and then subjected to heteroatom doping and calcination.

[0022] Further preferably, the surface oxidation-enriched treatment includes one or more of oxygen plasma treatment, acid solution heat treatment, and air heat treatment.

[0023] Preferably, the method for removing sulfur from the mixture is:

[0024] The mixture is dispersed in a good solvent for elemental sulfur and then separated, and the obtained solid is a carbon material with sulfur grafted on the surface.

[0025] The second purpose of the present invention is to protect the carbon material with surface grafted sulfur obtained by the preparation method.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. First, the present invention uses a two-step heat treatment, that is, nitrogen and / or sulfur atoms are doped into the surface of the carbon material at low temperature, and then the doped nitrogen and / or sulfur atoms are removed at high temperature to form a carbon material modified with surface topological defects. The topological defects have partial double bonds, which are conducive to the grafting of short-chain sulfur; by controlling the temperature of heteroatom doping and removal, the topological defect modification of the carbon material only occurs on the surface, and the concentration of topological defects on the surface of the carbon material is increased. The higher the concentration, the more active sites that can graft short-chain sulfur, and the corresponding grafted short-chain sulfur content is also higher. Then the carbon material modified with surface topological defects and elemental sulfur are heat-treated at a lower temperature to obtain a carbon material with surface grafted sulfur. The low-temperature heat treatment avoids the decomposition of elemental sulfur at too high a temperature. The elemental sulfur is opened at a lower temperature to form an active sulfur chain and react with the active topological defect, and is grafted on the surface of the carbon material in the form of a CS covalent bond, without the need to fix the active short-chain sulfur by means of cross-linking, group coupling, etc. Second, the method for grafting sulfur on the surface of a carbon material provided by the present invention has good universality and can be used for various common carbon materials. Third, the method for grafting sulfur on the surface of carbon materials provided by the present invention has a modification effect on both commercial carbon materials circulating on the market and homemade carbon materials. The preparation steps are simple, the material cost is low, and it has good cost-effectiveness and scale-up potential.

[0028] 2. The present invention also performs an oxygen-enriched treatment on the carbon material to introduce oxygen-enriched groups on the surface of the carbon material to increase the reaction sites during the doping process of nitrogen and / or sulfur atoms.

[0029] 3. When the prior art performs sulfur doping modification on carbon materials, polymers are grafted on the surface of the carbon materials, and the carbon materials themselves are still physically mixed with elemental sulfur; however, the present invention introduces short-chain sulfur composed of 2 to 6 sulfur atoms, which is grafted on the surface of the carbon materials in the form of CS covalent bonds, has higher reactivity and different reaction characteristics, and can be used as active reaction sites to induce chemical reactions or directly participate in chemical reactions. At the same time, this short-chain sulfur-grafted carbon material composited in the form of covalent bonds is also more stable than the general physical sulfur-blended carbon material, which is conducive to the carbon material showing better application potential in different fields. The carbon material with sulfur grafted on the surface prepared by the present invention has sulfur mainly distributed on the surface of the carbon material, and can basically retain the original internal structure of the carbon material (such as micropores for storing semi-metallic sodium). The active short-chain sulfur on the surface of the carbon material with surface grafted sulfur prepared by the present invention can participate in the formation of a solid electrolyte interface, so that when it is used as an electrode material of a secondary battery (taking a sodium ion battery as an example), it can form a more ideal solid electrolyte interface on the electrode surface, while retaining the original properties of the carbon material, so that sodium ions can be transmitted in the modified solid electrolyte interface, thereby improving the performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1Transmission electron microscope image (a) of the hard carbon with surface grafted sulfur prepared in Example 1 of the present invention and the corresponding sulfur element map image (b) ;

[0031] Figure 2 High-resolution transmission electron microscopy images of the hard carbon with surface grafted sulfur (a) and the raw material hard carbon (b) prepared in Example 1 of the present invention;

[0032] Figure 3 XRD spectra of the hard carbon with surface grafted sulfur and the raw material hard carbon prepared in Example 1 of the present invention, as well as the XRD card corresponding to the sulfur element;

[0033] Figure 4 The Raman spectra of the hard carbon with surface grafted sulfur prepared in Example 1 of the present invention and the raw material hard carbon;

[0034] Figure 5 When the hard carbon with surface grafted sulfur prepared in Example 1 of the present invention is subjected to XPS depth profiling analysis, the relative content of surface sulfur atoms changes with the increase of profiling time;

[0035] Figure 6 This is a time-of-flight secondary ion mass spectrometry analysis spectrum of the hard carbon with surface grafted sulfur prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] The technical solutions in the present invention will be described clearly and completely below in conjunction with the specific implementation of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The methods described in the embodiments of the present invention are conventional methods unless otherwise specified. The materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.

[0038] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. Among them, A and B can be singular or plural; the single symbol " / " means "or".

[0039] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of A, B or C", or "at least one of A, B and C" can represent any one of A, B, C, or A+B, or A+C, or B+C, or A+B+C, where A, B, C can be single or multiple, respectively.

[0040] In the following description of this embodiment, the order of serial numbers does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of this embodiment.

[0041] In the following description of the present embodiment, the numerical range should be understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Any stated value or intermediate value in the stated range and any other stated value or each smaller range between the intermediate values ​​in the stated range are also included in the present embodiment, and the upper and lower limits of the smaller range can be independently included or excluded in the range.

[0042] Unless otherwise stated, the technical / scientific terms used in the present embodiment have the same meanings as those generally understood by those skilled in the art to which the present application belongs. Although the present application only describes preferred methods and materials, any similar or equivalent methods and materials may also be used in the implementation or testing of the present application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of any conflict with any incorporated document, the content of this specification shall prevail.

[0043] Example 1

[0044] A method for preparing hard carbon with sulfur grafted on the surface comprises the following steps:

[0045] Step (1): Place 1.0g of hard carbon in a small beaker and treat it four times using an oxygen plasma treatment machine. Stir the powder evenly between each treatment. During the treatment, the vacuum degree is kept below 20Pa, the treatment power is 150W, and the treatment time is 4min to obtain hard carbon with surface oxidation treatment. Grind and mix the hard carbon with surface oxidation treatment and 1.0g of melamine powder evenly, and place it at 200mL min -1 In a nitrogen atmosphere, the -1 The heating rate was increased to 700°C and kept for 2 h, then increased to 1050°C and kept for 2 h, and then naturally cooled to room temperature and taken out to obtain hard carbon modified with surface topological defects.

[0046] Step (2): The hard carbon modified with surface topological defects obtained in step (1) and elemental sulfur were ground and mixed evenly in a mass ratio of 1:4, placed in a small glass bottle, sealed with aluminum foil, and placed at 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The heating rate is increased to 155°C and kept for 12 hours to allow the material and elemental sulfur to be evenly mixed, then increased to 200°C and kept for 6 hours. After naturally cooling to room temperature, the product is taken out and dispersed with carbon disulfide solution. After centrifugal separation, it is placed in a vacuum oven at 40°C and dried for 12 hours to obtain hard carbon with surface grafted sulfur.

[0047] Example 2

[0048] A method for preparing silicon carbon with sulfur grafted on the surface comprises the following steps:

[0049] Step (1): Place 1.0g of silicon carbon in a small beaker and treat it four times in an oxygen plasma treatment machine, with the vacuum degree maintained below 20Pa, the treatment power being 150W, and the treatment time being 4min. Stir the powder evenly between each treatment to obtain silicon carbon with surface oxidation treatment. Grind and mix the silicon carbon with surface oxidation treatment and 1.0g of melamine powder evenly, and place it at 200mL·min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 700°C and kept for 2 h, then raised to 1050°C and kept for 2 h, and then naturally cooled to room temperature and taken out to obtain silicon carbon modified with surface topological defects.

[0050] Step (2): Grind and mix the silicon carbon modified with surface topological defects obtained in step (1) and elemental sulfur in a mass ratio of 1:0.5, place in a small glass bottle, seal with aluminum foil, and place at 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The heating rate is increased to 155°C and kept for 12 hours to allow the material and elemental sulfur to be evenly mixed, then the temperature is increased to 200°C and kept for 6 hours. After naturally cooling to room temperature, the product is taken out and dispersed with carbon disulfide solution. After centrifugal separation, it is placed in a vacuum oven at 40°C and dried for 12 hours to obtain silicon carbon with surface grafted sulfur.

[0051] Example 3

[0052] A method for preparing carbon nanotubes with surface grafted sulfur comprises the following steps:

[0053] Step (1): Place 1.0g of carbon nanotubes in a small beaker and treat them four times in an oxygen plasma treatment machine, with the vacuum degree maintained below 20Pa, the treatment power being 150W, and the treatment time being 4min. Stir the powder evenly between each treatment to obtain carbon nanotubes with surface oxidation treatment. Grind and mix the carbon nanotubes with surface oxidation treatment and 1.0g of melamine powder evenly, and place them at 200mL·min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 700°C and kept for 2 h, then raised to 1050°C and kept for 2 h, and then naturally cooled to room temperature and taken out to obtain carbon nanotubes modified with surface topological defects.

[0054] Step (2): The carbon nanotubes modified with surface topological defects obtained in step (1) and elemental sulfur were ground and mixed evenly at a mass ratio of 1:8, placed in a small glass bottle, sealed with aluminum foil, and placed at 200 mL min. -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The heating rate was raised to 155°C and kept for 12 hours to allow the material and elemental sulfur to be evenly mixed, then raised to 200°C and kept for 6 hours. After naturally cooling to room temperature, the product was taken out and dispersed with carbon disulfide solution. After centrifugal separation, it was placed in a vacuum oven at 40°C and dried for 12 hours to obtain carbon nanotubes with surface grafted sulfur.

[0055] Example 4

[0056] A method for preparing hard carbon with sulfur grafted on the surface comprises the following steps:

[0057] Step (1): Place 1.0 g of hard carbon in a small beaker and treat it four times in an oxygen plasma treatment machine. Keep the vacuum degree below 20 Pa, the treatment power is 150 W, and the treatment time is 4 min. Stir the powder evenly between each treatment to obtain hard carbon with surface oxidation treatment. Grind and mix the hard carbon with surface oxidation treatment and 1.0 g of melamine powder evenly, and place it at 200 mL min. -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The heating rate was increased to 700°C and kept for 2 h, then increased to 1050°C and kept for 2 h, and then naturally cooled to room temperature and taken out to obtain hard carbon modified with surface topological defects.

[0058] Step (2): The hard carbon modified with topological defects obtained in step (1) and sulfur were ground and mixed evenly in a mass ratio of 1:10, placed in a small glass bottle, sealed with aluminum foil, and placed at 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1The heating rate is increased to 155°C and kept for 12 hours to allow the material and elemental sulfur to be evenly mixed, then increased to 300°C and kept for 6 hours. After naturally cooling to room temperature, the product is taken out and dispersed with carbon disulfide. After centrifugal separation, it is placed in a vacuum oven at 40°C and dried for 12 hours to obtain hard carbon with surface grafted sulfur.

[0059] Comparative Example 1 (no surface topological defect modification, direct heat treatment of carbon material and sulfur element)

[0060] A method for preparing modified hard carbon comprises the following steps:

[0061] 1.0 g of hard carbon and sulfur were ground and mixed evenly in a mass ratio of 1:4, placed in a small glass bottle, sealed with aluminum foil, and placed at 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The heating rate is raised to 155°C and maintained for 12 hours to allow the material and elemental sulfur to be evenly mixed to obtain modified hard carbon.

[0062] Comparative Example 2 (physical mixing of surface topological defect modified carbon material and sulfur element)

[0063] A method for preparing modified hard carbon comprises the following steps:

[0064] Step (1): Place 1.0 g of hard carbon in a small beaker and treat it four times in an oxygen plasma treatment machine. Keep the vacuum degree below 20 Pa, the treatment power is 150 W, and the treatment time is 4 min. Stir the powder evenly between each treatment to obtain hard carbon with surface oxidation treatment. Grind and mix the hard carbon with surface oxidation treatment and 1.0 g of melamine powder evenly, and place it at 200 mL min. -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The heating rate was increased to 700°C and kept for 2 h, then increased to 1050°C and kept for 2 h, and then naturally cooled to room temperature and taken out to obtain hard carbon modified with surface topological defects.

[0065] Step (2): Grind and mix the surface-oxidized hard carbon obtained in step (1) and elemental sulfur in a mass ratio of 1:4 to obtain modified hard carbon.

[0066] Performance Testing:

[0067] Since the modified hard carbons prepared in Comparative Example 2 and Comparative Example 1 are physically mixed and have basically the same performance, only the modified hard carbon prepared in Comparative Example 1 is tested below. The surface-grafted sulfur carbon materials prepared in Examples 2 to 4 and Example 1 have basically the same performance, and only the surface-grafted sulfur carbon material prepared in Example 1 is tested below.

[0068] Effect Example 1

[0069] In order to further illustrate the beneficial effects of the present invention, the hard carbon with surface grafted sulfur obtained in Example 1 was characterized by transmission electron microscopy. Figure 1 (a); and elemental map representation, see Figure 1 (b). For the hard carbon with sulfur grafted on the surface obtained in Example 1, see Figure 2 (a) and the raw hard carbon were characterized by high-resolution transmission electron microscopy. Figure 2 (b). Figure 1 As shown in FIG. 1 , the sulfur-grafted hard carbon obtained in Example 1 has a uniform distribution of sulfur on its surface. Figure 2 As shown, the internal graphite sheet structure of the hard carbon with surface grafted sulfur prepared in Example 1 is basically consistent with that of the raw material hard carbon. This shows that the sulfur of the hard carbon with surface grafted sulfur prepared in the present invention is mainly distributed on the surface of the carbon material, and the original internal structure of the carbon material can be basically retained.

[0070] Effect Example 2

[0071] In order to further illustrate the beneficial effects of the present invention, the hard carbon with surface grafted sulfur and the raw material hard carbon prepared in Example 1 were characterized by X-ray diffraction. Figure 3 , and Raman spectroscopy characterization, see Figure 4 . Figure 3 These are the XRD spectra of the hard carbon with surface grafted sulfur prepared in Example 1 and the raw material hard carbon. No crystal plane peak corresponding to elemental sulfur appears in the XRD spectrum, indicating that the hard carbon with surface grafted sulfur prepared in Example 1 has no residual elemental sulfur, and its basic structure remains consistent with the raw material. Figure 4 The Raman spectra of the hard carbon with surface grafted sulfur prepared in Example 1 and its raw material hard carbon are basically consistent with the XRD spectrum, which shows that the hard carbon with surface grafted sulfur prepared in the present invention has sulfur mainly distributed on the surface of the carbon material and can basically retain the original internal structure of the carbon material.

[0072] Effect Example 3

[0073] In order to further illustrate the beneficial effects of the present invention, XPS depth analysis was performed on the hard carbon with surface grafted sulfur obtained in Example 1, and the relative content of sulfur atoms on the surface of the samples at different analysis times was quantitatively analyzed. Figure 5 As shown, the surface of the hard carbon grafted with sulfur prepared in Example 1 has a sulfur content of 3.83 at%. As the analysis time increases, the sulfur content first increases and then decreases, and finally decreases to 0.66 at%. The reason for the increase in sulfur content at the analysis time of 10 s may be that there are a small amount of oxygen atoms on the surface of the sample, which reduces the relative content of sulfur atoms. The above results show that the sulfur element contained in the hard carbon grafted with sulfur prepared in Example 1 is mainly distributed on the surface of the material, and will not affect the pore structure and graphitization degree of the carbon electrode.

[0074] Effect Example 4

[0075] In order to further illustrate the beneficial effects of the present invention, the hard carbon with surface grafted sulfur prepared in Example 1 was analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS). Figure 6 As shown, the surface of the hard carbon with surface grafted sulfur prepared in Example 1 has different sulfur-containing molecules, including small molecules composed of 2 to 6 sulfur atoms. The above results show that the surface of the hard carbon with surface grafted sulfur prepared in Example 1 contains short-chain sulfur, while the grafted carbon nanotube / sulfur composite positive electrode material prepared in the prior art, the carbon material itself and the elemental sulfur are still physically mixed in the composite. Therefore, the existence form of sulfur atoms on the hard carbon with surface grafted sulfur prepared by the present invention is completely different from the form of sulfur atoms doped in the conventional carbon skeleton, and has higher reactivity.

[0076] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0077] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a carbon material with sulfur grafted on the surface, characterized in that: include: In a protective gas, the carbon material is doped with nitrogen-containing small molecules and / or sulfur-containing small molecules at 600-800° C. and calcined at 900-1400° C. to obtain a carbon material with surface topological defects modified; In a protective gas, the prepared carbon material modified with surface topological defects is mixed with sulfur element and then heat treated at 150-400° C. for 4-40 hours to obtain a carbon material with surface grafted sulfur.

2. The method for preparing the carbon material with surface grafted sulfur according to claim 1, characterized in that: The mass ratio of the nitrogen-containing small molecules and / or sulfur-containing small molecules to the carbon material is 1:0.5-2.

3. The method for preparing the carbon material with surface grafted sulfur according to claim 1, characterized in that: The nitrogen-containing small molecules and / or sulfur-containing small molecules are one or more of melamine, urea, thiourea, cyanamide and dicyandiamide.

4. The method for preparing the carbon material with surface grafted sulfur according to claim 1, characterized in that: The carbon material is one or more of hard carbon, soft carbon, graphite, nano carbon material, and silicon carbon.

5. The method for preparing the carbon material with surface grafted sulfur according to claim 1, characterized in that: The heteroatom doping heat preservation time is 1 to 4 hours, and the calcination heat preservation time is 1 to 4 hours.

6. The method for preparing the carbon material with surface grafted sulfur according to claim 1, characterized in that: The mass ratio of the carbon material modified with surface topological defects to sulfur is 1:0.5-10.

7. The method for preparing the carbon material with surface grafted sulfur according to claim 1, characterized in that: The prepared surface topological defect modified carbon material is mixed with sulfur element and then heat treated at 150-180° C. for 2-20 hours, and then heat treated at 200-400° C. for 2-20 hours.

8. The method for preparing the carbon material with surface grafted sulfur according to claim 1, characterized in that: The carbon material is first subjected to surface oxidation enrichment treatment, and then subjected to heteroatom doping and calcination.

9. The method for preparing a carbon material with surface grafted sulfur according to claim 8, characterized in that: The surface oxidation treatment includes one or more of oxygen plasma treatment, acid solution heat treatment, and air heat treatment.

10. A carbon material with surface grafted sulfur obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Grafted carbon nanotube / sulfur composite positive electrode material having high specific capacity and long cycle life

    CN103247786A